2014
DOI: 10.3389/fncel.2014.00056
|View full text |Cite
|
Sign up to set email alerts
|

The free radical scavenger Trolox dampens neuronal hyperexcitability, reinstates synaptic plasticity, and improves hypoxia tolerance in a mouse model of Rett syndrome

Abstract: Rett syndrome (RS) causes severe cognitive impairment, loss of speech, epilepsy, and breathing disturbances with intermittent hypoxia. Also mitochondria are affected; a subunit of respiratory complex III is dysregulated, the inner mitochondrial membrane is leaking protons, and brain ATP levels seem reduced. Our recent assessment of mitochondrial function in MeCP2 (methyl-CpG-binding protein 2)-deficient mouse (Mecp2-/y) hippocampus confirmed early metabolic alterations, an increased oxidative burden, and a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 77 publications
7
47
2
Order By: Relevance
“…Neither TBS nor pairing low-frequency stimulation with postsynaptic depolarization were able to induce LTP at hippocampal CA1 synapses of Mecp2 KO mice, as shown previously with tetanic high-frequency stimulation in different MeCP2-deficient models (6)(7)(8)(9)(10). The potentiation of the amplitude and spatial spread of VSD signals observed after TBS in WT slices is absent in Mecp2 KO slices.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Neither TBS nor pairing low-frequency stimulation with postsynaptic depolarization were able to induce LTP at hippocampal CA1 synapses of Mecp2 KO mice, as shown previously with tetanic high-frequency stimulation in different MeCP2-deficient models (6)(7)(8)(9)(10). The potentiation of the amplitude and spatial spread of VSD signals observed after TBS in WT slices is absent in Mecp2 KO slices.…”
Section: Discussionsupporting
confidence: 43%
“…The visual cortex of Mecp2 KO mice shows a similar reduction of pyramidal neuron and network activity but caused by stronger inhibition due to hyperinnervation of parvalbumin interneurons (38). Neuronal activity is elevated in the hippocampus (7,8,15,(39)(40)(41) and brainstem (42-44) of Mecp2 KO mice. Enhanced synaptic transmission and spatiotemporal spread of neuronal depolarizations in CA1 is due to higher spontaneous activity of CA3 pyramidal neurons in Mecp2 KO hippocampal slices (15).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As a crucial control, we asked whether NADH and FAD autofluorescence may interfere with roGFP1 imaging as neuronal activity and mitochondrial metabolism also modulate the levels of these electron carriers and since similar excitation wavelengths (NADH 360 nm, FAD 445 nm) are used to monitor their tissue autofluorescence (26,32). Tests on WT slices with identical wavelengths and filter settings and similar ROIs used for roGFP imaging showed that electrical stimulation (100 Hz, 3 min) indeed increased NADH fluorescence (exc.…”
Section: Modifying Endogenous Ros Formation and Redox Regulationmentioning
confidence: 99%